Targeting DNA Repair Response Promotes Immunotherapy in Ovarian Cancer: Rationale and Clinical Application - Xie, Hongyu; Wang, Wenjie; Qi, Wencai; Jin, Weilin; Xia, Bairong (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICI) have emerged as a powerful oncologic treatment modality for patients with different solid tumors. Unfortunately, the efficacy of ICI monotherapy in ovarian cancer is limited, and combination therapy provides a new opportunity for immunotherapy in ovarian cancer. DNA damage repair (DDR) pathways play central roles in the maintenance of genomic integrity and promote the progression of cancer. Deficiency in DDR genes can cause different degrees of DNA damage that enhance local antigen release, resulting in systemic antitumor immune responses. Thus, the combination of DDR inhibitors with ICI represents an attractive therapeutic strategy with the potential to improve the clinical outcomes of patients with ovarian cancer. In this review, we provide an overview of the interconnectivity between DDR pathway deficiency and immune response, summarize available clinical trials on the combination therapy in ovarian cancer, and discuss the potential predictive biomarkers that can be utilized to guide the use of combination therapy.